An interdisciplinary intervention for children with complex health complaints; a feasibility study of selection criteria - Elgen, Irene; Lygre, Ragnhild B; Årli, Ånen; Heggestad, Torhild (Frontiers in Pediatrics, 2023)
Background There is a need for re-designing the health service for children suffering from complex and compound health complaints. Based on a previous register study, we have developed criteria to select patients with complex health complaints eligible for an Intervention with an interdisciplinary professional team. The team consists of a pediatrician, a psychologist and a physiotherapist. Method To identify children with complex health complaints who would benefit from this intervention, we have selected a group of patients by using a set of criteria consisting of the following criteria: multi-referred young school age children referred to both mental health service and pediatric service. This study focuses on the feasibility of these criteria by measuring participation and compliance and by gathering feedback from the team members in the interdisciplinary team. Results Among 677 children aged 6−12 years referred to a regional hospital, we found 32 (5%) children eligible for the interdisciplinary Intervention according to the applied criteria. Only 6% of the invited parents declined to participate in the intervention. According to the interdisciplinary team, the intervention was found suitable for 88% of the children. Conclusion The suggested criteria seemed feasible, in terms of identifying eligible patients for this interdisciplinary Intervention for children with complex health complaints. Clinical Trial Registration Retrospectively registered on www.clinicaltrials.gov, ID NCT04652154, on the 3rd of December 2020.